2023
DOI: 10.4093/dmj.2023.0112
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Sarcopenia as Comorbid Chronic Diseases in Older Adults: Established and Emerging Treatments and Therapies

Jakub Mesinovic,
Jackson J. Fyfe,
Jason Talevski
et al.

Abstract: Type 2 diabetes mellitus (T2DM) and sarcopenia (low skeletal muscle mass and function) share a bidirectional relationship. The prevalence of these diseases increases with age and they share common risk factors. Skeletal muscle fat infiltration, commonly referred to as myosteatosis, may be a major contributor to both T2DM and sarcopenia in older adults via independent effects on insulin resistance and muscle health. Many strategies to manage T2DM result in energy restriction and subsequent weight loss, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 264 publications
0
2
0
1
Order By: Relevance
“…A great deal of evidence suggests that a bidirectional association between sarcopenia and T2DM contributes to a vicious cycle of mutual aggravation, ultimately resulting in poor quality of life and serious health outcomes. T2DM is an important etiological factor for the development of sarcopenia, as evidenced by various studies that have demonstrated a notable prevalence of sarcopenia in individuals with T2DM . In contrast, the degeneration of skeletal muscle in sarcopenia patients deteriorates glucose metabolism and further increases the risk of T2DM development .…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of evidence suggests that a bidirectional association between sarcopenia and T2DM contributes to a vicious cycle of mutual aggravation, ultimately resulting in poor quality of life and serious health outcomes. T2DM is an important etiological factor for the development of sarcopenia, as evidenced by various studies that have demonstrated a notable prevalence of sarcopenia in individuals with T2DM . In contrast, the degeneration of skeletal muscle in sarcopenia patients deteriorates glucose metabolism and further increases the risk of T2DM development .…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, при оценке механизмов влияния тестостерона на метаболические показатели неоднократно сообщалось о его положительном влиянии на состав тела с повышением тощей массы за счет активации сателлитных клеток скелетных мышц, фактора роста фибробластов 2, снижения экспрессии супрессоров мышечного роста, миостатина, миогенного регуляторного фактора 4; липолитическим действием с уменьшением свободных жирных кислот, маркеров асептического воспаления (СРБ, ФНО-α, интерлейкин-1β) [8,24,26]. Так, по данным наиболее крупных исследований мужчин как с возрастным андрогенным дефицитом, так и с гипогонадизмом на фоне ожирения и/или СД2, ТЗТ была связана со значимым снижением содержания жира и увеличением либо сохранением мышечной массы, а также со снижением гликемии натощак и резистентности к инсулину [27,28,29]. Вышеизложенные данные литературы согласуются с полученными нами результатами о статистически значимо большем снижении ОТ, но не ИМТ, на фоне ТЗТ по сравнению с контрольной группой, что косвенно отражает потерю висцеральной жировой ткани при сохранении мышечной массы.…”
Section: обсуждение основных результатов исследованияunclassified
“…Diabetic sarcopenia (DS), considered as a complication of diabetes, leads to an increased risk of falls, fractures, physical disabilities, and even mortality. The condition severely impacts the quality of life for those diabetic patients and escalates the economic burden on the country, society, and families . Numerous studies have identified hyperglycemia, insulin resistance, oxidative stress, and inflammation as pivotal factors in the development and progression of DS. , The precise molecular mechanisms underlying DS are complex and need further exploration.…”
Section: Introductionmentioning
confidence: 99%